Food intake in women two years or more after bariatric surgery meets adequate intake requirements - Sousa Novais, Patricia Fatima [UNESP]; Rasera, Irineu [UNESP]; de Souza Leite, Celso Vieira [UNESP]; Marin, Flavia Andreia [UNESP]; Oliveira, Maria Rita Marques [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
Restricted food intake after bariatric surgery can be an important factor both in the long-term control of body weight and in the onset of nutritional deficiencies. The objective of this study was to assess the adequacy of food intake in women two or more years after bariatric surgery according to the excess weight lost. A group of 141 women who underwent banded Roux-en-Y gastric bypass (RYGB) was divided according to the percentage of excess weight they lost (%EWL)<50; 50-175; = 75. The habitual energy and nutrient intakes were determined by a 24-hour recall over two days and the probability of adequate intake was based on the Dietary Reference Intake. The mean total estimated energy requirement (EER) as well as energy, macronutrient and cholesterol intakes did not differ among the groups. Only the %EWL < 50 group had an intake equal to their EER, but they presented a higher number of inadequacies, such as low levels of magnesium, folic acid and vitamins C and E. Calcium and dietary fiber intakes were extremely low in all three groups. In conclusion, weight loss after surgery is associated with food habits that favor energy intake over micronutrient intake. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Morbid obesity; Bariatric surgery; Food intake; Excess weight loss; Micronutrients; Women